Microorganism-induced suppression of allergic airway disease: novel therapies on the horizon?. (December 2014) - Obieglo, Katja; van Wijck, Yolanda; de Kleijn, Stan; Smits, Hermelijn H; Taube, Christian
<x xml:space="preserve">Abstract</x> Allergic airway disease is a major global health burden, and novel treatment options are urgently needed. Numerous epidemiological and experimental studies suggest that certain helminths and bacteria protect against respiratory allergies. These microorganisms are strong regulators of the immune system, and various potential regulatory mechanisms by which they protect against allergic airway inflammation have been proposed. Whereas early studies addressed the beneficial effect of natural infections, the focus now shifts toward identifying the dominant protective molecules and exploring their efficacy in models of allergic airway disease. In this article, we will review the evidence for microbe-mediated protection from allergic airway disease, the potential modes of action involved and discuss advances as well as limitations in the translation of this knowledge into novel treatment strategies against allergic airway disease.